Improving Employee Performance Based on Social Capital and Information Technology with Employee Engagement as Mediation - Trisninawati Trisninawati; Vivi Sahfitri; Andrian Noviardy (Economic Education Analysis Journal, 2025)
This study aims to analyze the improvement of team member performance based on social capital and information technology with team member engagement as a mediator (a case study of millennial generation employees of MSMEs in Palembang city). This research was conducted with a quantitative approach. This method is used to examine data on populations and samples by collecting data through research instruments and analyzing the data quantitatively. The subjects in the study were Millennial Generation employees. The location of this research was several types of work in MSMEs in Palembang city. The method used in drawing samples in this study was purposive sampling. The sample in this study was 80 employees of the millennial generation. Research hypothesis testing used the Structural Equation Modeling (SEM) approach using AMOS version 24. The results of the study indicate that social capital has no significant effect, information technology has a considerable effect, and team member engagement substantially impacts the performance of millennial generation employees. Furthermore, social capital and information technology are having a significant impact on millennial generation team member engagement. Meanwhile, team member engagement mediates the effect of social capital and information technology on millennial generation team member performance. Based on the findings in this study, future research adds new variables that have not been studied to enrich the study of the current Millennial Generation team member performance.